An evaluation of tablet-based apps for maths learning in young children with Down's Syndrome - Allison, Kate (2019)
Raising mathematical attainment in primary school education is important nationally, particularly for students who have Special Educational Needs (SEN). Tablet technology is an accessible and practical platform to provide additional teaching and raise learning outcomes (Haßler, Major & Hennessy, 2015). A literature review, including a systematic search of the use of tablet-based apps in raising maths attainment for children with SEN, provides a critical review of the existing theory and evidence base. The present study evaluates the impact of tablet-based maths applications (apps) for children in Key Stage One of mainstream school who have Down’s Syndrome (DS). A case study methodology, with embedded single case experimental designs (SCEDs), was implemented to explore the effects of daily fifteen-minute use of the onebillion maths apps supported by a teaching assistant (TA), on maths attainment and engagement with maths learning. The learner’s level of functioning and pre and post measures of maths attainment were triangulated. Qualitative data from interviews with the facilitators was used to explore their perceptions of the intervention’s effects for children with DS, as well the factors affecting its implementation and accessibility. Outcomes varied across participants, with three out of four cases engaging well the intervention and displaying a positive effect size in one of two repeated measures, analysed using visual analysis and effect size; maths attainment or engagement. Relationships within the data were observed that suggested the outcomes of the intervention were influenced by the child’s pre-requisite skills and level of functioning. Facilitators’ perceptions of the app were positive, sharing views that children had enjoyed their time spent learning on the app and reporting gains in a range of skills including maths knowledge, confidence and patience in the children. A discussion of factors affecting outcomes identifies a range of individual and environmental aspects; and features of the intervention. Results are considered in relation to existing research and its theoretical explanations. A review of the design and analysis used, acknowledges design threats which influence the conclusions that can be drawn. Implications for the use of tablet-based maths learning for children with SEN, future research and educational psychology are outlined.